PEMBELAJARAN SENAM LANTAI FORWARD ROLL DAN BACKWARD ROLL MELALUI PENDEKATAN PEMBELAJARAN TAKTIS - yarso, Herkanda; G Simanjuntak, Victor; Haetami, Mimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe problem that arises was how much a tactical learning approach contributes to the forward roll and backward roll gymnastic learning. The purpose of this study was to find out how big the tactical learning approach contributes to the forward roll and backward roll gymnastic learning. The method used in this study was quantitative in the form of pre-experimental design. The population in this study were 60 students in class X. Sampling used a total sampling technique that was class XA students totaling 30 people, the data analysis technique used was the t-test analysis. The results of the study before being given treatment, the lowest score 27 and the highest score 81 with an average of 52.5 on the forward roll skills for backward roll scores obtained, namely the lowest score of 18 and the highest score of 72 with an average of 45.9. Based on these conclusions, forward roll and backward roll gymnastic learning through tactical approach learning can help students improve motion efficiency and help teachers in teaching was very appropriate for delivering learning material at school.Keywords: Floor Gymnastic, Tactical Learning